ANALYSIS OF A ROLL BENDING MACHINE: ENHANCING EFFICIENCY AND FUNCTIONALITY - Mongia GAAIA; Petruta PETCU; Ana-Maria NICOLAU (Journal of Industrial Design and Engineering Graphics)
Abstract: This study delves into the analysis of roll bending machines, which are indispensable in the sheet metal forming industry. The primary goal is to investigate the diverse characteristics and versions of roll bending machines available in the market and to propose enhancements to boost their efficiency. Through an in-depth analysis of the current systems and an exploration of potential improvements, especially regarding the upper roll's transmission system, this research aims to optimize the operational performance of roll bending machines. Additionally, an internal functional analysis is conducted to provide a thorough understanding of the product and its mechanics, focusing on improving reliability, product quality, and costeffectiveness.